# Differential Equation Formulas

Need to solve all complex Differential Equation problems easily? Then, using the Differential Equation Formulas is the best way. You can simplify Linear Differential Equations, Differential Equation of Homogeneous Type, and many other concepts problems easily by using the list of Differential Equation Formulas provided over here. You will discover various Differential Equation formulas on this page. So, go through the further sections and get the Differential Equation Formulae List & Tables for free.

## Differential Equation Formulas Sheet

The concept of differential equations is used in various fields of the real-world like physics, engineering, and economics. To make your calculations on Differential Equations easily use the provided list of Differential Equation formulas. Also, stick the Differential Equation Formula Sheet on the wall at study place and memorize them regularly.

**1. Differential Equation**

An equation containing an independent variable, dependent variable and differential coefficients of dependent variable with respect to independent variable is called a differential equation.

**2. Order of Differential Equation**

The order of a differential equation is the order of the highest derivative occurring in the differential equation.

**3. Degree of Differential Equation**

The degree of a differential equation is the degree of the highest order derivative when differential coefficients are free from radical and fractional power.

**4. General solution**

The solution which contains a number of arbitrary constants equal to the order of the equation is called general solution or complete integral or complete primitive of differential equation.

**5. Differential Equations of the Form \(\frac{d y}{d x}\) = f(x)**

∫ dy = ∫ f(x) dx + c

**6. Differential Equations of the Form \(\frac{d y}{d x}\) = f(x) g(y)**

(variable separable pattern)

∫ \(\frac{d y}{g(y)}\) = ∫ f(x) dx + c

**7. Differential Equations of the Form of \(\frac{d y}{d x}\) = f (ax + by + c)**

To solve this type of differential equations, we put ax + by + c = v and

\(\frac{d y}{d x}=\frac{1}{b}\left(\frac{d v}{d x}-a\right)\)

∴ \(\frac{d v}{a+b f(v)}\) = dx

So solution is by integrating ∫\(\frac{d v}{a+b f(v)}\) = ∫ dx

**8. Differential Equation of Homogeneous Type or f(y/x) = 0 pattern**

To solve the homogeneous differential equation \(\frac{d y}{d x}=\frac{f(x, y)}{g(x, y)}\),

substitute y = vx and so \(\frac{d y}{d x}\) = v + x \(\frac{d v}{d x}\)

Thus v + x \(\frac{d y}{d x}\) = f( v) ⇒ \(\frac{d x}{x}\) = \(\frac{d v}{f(v)-v}\)

Therefore solution is \(\int \frac{d x}{x}=\int \frac{d v}{f(v)-v}+c\)

**9. Differential Equations reducible to Homogeneous Form**

A differential equation of the form \(\frac{d y}{d x}=\frac{a_{1} x+b_{1} y+c_{1}}{a_{2} x+b_{2} y+c_{2}}\), where \(\frac{a_{1}}{a_{2}} \neq \frac{b_{1}}{b_{2}}\) can be reduced to homogeneous form by adopting the following procedure –

put x = X + h, y = Y + kso that = \(\frac{d Y}{d X}=\frac{d y}{d x}\)

The equation then transformed to

\(\frac{d Y}{d X}=\frac{a_{1} X+b_{1} Y+\left(a_{1} h+b_{1} k+c_{1}\right)}{a_{2} X+b_{2} Y+\left(a_{2} h+b_{2} k+c_{2}\right)}\)

Now choose h and k such that a_{1}h + b_{1}k + c_{1} = 0 and a_{2}h + b_{2}k + c_{2} = 0.

Then for these values of h and k the equation becomes \(\frac{d Y}{d X}=\frac{a_{1} X+b_{1} Y}{a_{2} X+b_{2} Y}\)

This is a homogeneous equation which can be solved by putting Y = vX and then Y and X should be replaced by y – k and x – h.

**10. Linear Differential Equations**

A differential equation is linear if the dependent variable (y) and its derivative appear only in first degree. The general form of a linear differential equation of first order is \(\frac{d y}{d x}\) + Py = Q

y e^{∫Pdx} = ∫Qe^{∫Pdx}dx + c

which is the required solution, where c is the constant and e^{∫Pdx} is called the integrating factor.

**11. Equation reducible to linear form [Bernoulli’s equation]**

If the given equation is of the form \(\frac{d y}{d x}p\) + P. f(y) = Q. g(y), where P

and Q are functions of x along, we divide the equation by g(y), we get

\(\frac{1}{g(y)} \frac{d y}{d x}+P \cdot \frac{f(y)}{g(y)}\)

Now substituted = \(\frac{f(y)}{g(y)}\) = v and solve same as method given in linear

differential equation.

12. Differential Equation in the form of \(\frac{d^{2} y}{d x^{2}}\) = f(x)

then its solution can be obtained by integrating it with respect to x twice.

**13. Some important results (solution by inspection)**

- d(xy) = xdy + ydx
- d\(\left(\frac{x}{y}\right)\) = \(\frac{y d x-x d y}{y^{2}}\), y ≠ 0
- d\(\left(\frac{y}{x}\right)\) = \(\frac{x d y-y d x}{x^{2}}\), x ≠ 0
- d\(\left(\frac{x^{2}}{y}\right)\) = \(\frac{2 x y d x-x^{2} d y}{y^{2}}\), y ≠ 0
- d\(\left(\frac{y^{2}}{x}\right)\) = \(\frac{2 x y d y-y^{2} d x}{x^{2}}\)
- d\(\left(\frac{x^{2}}{y^{2}}\right)\) = \(\frac{2 x y^{2} d x-2 x^{2} y d y}{y^{4}}\)
- d\(\left(\tan ^{-1}\left(\frac{y}{x}\right)\right)\) = \(\frac{x d y-y d x}{x^{2}+y^{2}}\)
- d(log
_{e}(xy)) = \(\frac{x d y+y d x}{x y}\) - d\(\left(\log _{e}\left(\frac{x}{y}\right)\right)\) = \(\frac{y d x-x d y}{x y}\)